AN INVESTIGATION INTO THE FACTORS INFLUENCING THE PARTICIPATION OF BLACK FEMALE TECHNICAL AND VOCATIONAL EDUCATION AND TRAINING (TVET) STUDENTS IN SOUTHERN KWAZULU-NATAL (KZN) IN SOUTH AFRICA - Nkala, Ayanda Lydia; Madikizela-Madiya, Nomanesi; Ngundu, Marvellous (Jurnal Pendidikan Ilmu Sosial, 2024)
This study aims to identify the factors influencing the participation of black female TVET students, using a case of a TVET college in Southern KZN. It adopts a human development approach to understand the capabilities, freedoms, and functionings available to black female students at this specific TVET college. The study was prompted by high dropout rates among black female TVET students and a disproportionate gender profile in skills programs. Furthermore, it contends that empowering black female students with capabilities allows them to express what they value and have gained from TVET colleges, not only in their current lives but also in their future lives. This is crucial for addressing the prevailing gender disparities in the country. The study was conducted using a descriptive case study design, and the data was gathered through semistructured interviews with final-year black female engineering and primary agriculture students at ABC (pseudonym) TVET College. The data was analyzed thematically, with data collection concluding after reaching saturation with ten participants. Surprisingly, the findings indicate that, in this particular college, the participation of black female students is not necessarily low. Therefore, gender no longer serves as a barrier to the participation of black female TVET students in skills programs at the college. Instead, the students effectively juggle their educational responsibilities with domestic chores while exerting considerable effort to participate and excel in their studies. This showcases women's ability to exercise agency despite facing constraints in their opportunities. The study recommends addressing the persistent societal perception that domestic chores are solely the responsibility of women to enhance women’s participation in their educational pursuits.